Politics of Constructing Islam in the Everyday Lives of Young Bangladeshis: Asserting Majoritarian Islam, and the "Good / Bad Muslim" Narrative. (April 2023) - Hasan, Mubashar; Bose, Srinjoy
This research paper examines how Bangladeshi youth perceive the role of Islam in their everyday lives and how this, in turn, informs broader political participation and radicalism. The emphasis is on unpacking the politics of meaning-making of Islam at the informal and individual levels eschewing a "high politics" approach that constitutes formal institutions and structures. Drawing on field-data collected in 2017 and 2018, this paper offers insights on the politics of faith in the everyday lives of ordinary Bangladeshi youths whose individual socio-political actions are inspired by their perception of what Islam is but not devoid from the influence of structures of high politics that constantly shapes and reshapes these individuals' perception of Islam. The findings indicate that divisions exist among young Bangladeshis about what Islam constitutes and means. Specifically, it was observed that an emerging trend is to advance the idea of Islam as a majoritarian religion through signs, symbols, and the politics of space. Within this context, narratives of "good Muslim" and "bad Muslim" manifest and contribute into justifications for radicalisation and even terror activities.